Study of Bali cattle physiological parameters during sea transport on camara nusantara ships - Adam Kustiadi Nugraha; Rudi Afnan; Epi Taufik; Aryani Sismin Satyaningtijas (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
There have never been specific research or study about cattle health during shipment using a Camara Nusantara ship as a mode of transportation. The objective of this study was to investigate the ship environment and physiological responses of cattle during transport from Tenau Port (Kupang) to Tanjung Priok Port (Jakarta) using Camara Nusantara 3 ship. The sample of 12 Bali cattle was determined using the purposive sampling total of 250 Bali cattle during transportation. Physiological parameters (including rectal temperature, respiratory rate, pulse rate) were used to evaluate the welfare status and stress level of animals, during the respective transport journeys. Transient changes in physiological parameters were found in the transported animals from day 2 to 4 relative to baseline levels, and the values were within the mild stress level of physiological range for the age of animals involved. There were significant differences (P<0.05) in rectal temperature, humidity, and temperature humidity index (THI). Using factorial Analysis of variance (ANOVA), there was an interaction between deck and day trip in the respiratory rate parameter. The cattle regained their initial normal range of physiological level and had slightly recovered by the time of their arrival on the 5th day of the journey.